2012
DOI: 10.1002/chem.201102139
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Asymmetric Hemithioacetal Transformation by Lipase‐Catalyzed γ‐Lactonization: In Situ Tandem Formation of 1,3‐Oxathiolan‐5‐one Derivatives

Abstract: Dynamic hemithioacetal systems were efficiently generated in organic solvents and subsequently allowed to react with a range of lipases. This resulted in direct, dynamic asymmetric transformation of the systems, leading to optically active 1,3-oxathiolan-5-one products. The tandem process identified lipase-catalyzed lactonization as a useful method for the resolution of optimal constituents with high chemo- and stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 52 publications
1
33
0
2
Order By: Relevance
“…Similarly, esters of optically pure hemithioacetals may be obtained by lipase-catalyzed transesterification of the respective hemithioacetal formed by reversible reaction from aldehydes and thiols (Brand et al, 1995;Hu et al, 2014;Sakulsombat et al, 2012a;Sanfilippo et al, 2005;Zhang et al, 2014a). This approach has proven to be useful for the preparation of optically pure 1,3-oxathiolan-5-ones, structural motifs that are featured in antiretroviral drugs (Fig.…”
Section: Dynamic Kinetic Resolution Of Cyanohydrins Hemiacetals and mentioning
confidence: 99%
“…Similarly, esters of optically pure hemithioacetals may be obtained by lipase-catalyzed transesterification of the respective hemithioacetal formed by reversible reaction from aldehydes and thiols (Brand et al, 1995;Hu et al, 2014;Sakulsombat et al, 2012a;Sanfilippo et al, 2005;Zhang et al, 2014a). This approach has proven to be useful for the preparation of optically pure 1,3-oxathiolan-5-ones, structural motifs that are featured in antiretroviral drugs (Fig.…”
Section: Dynamic Kinetic Resolution Of Cyanohydrins Hemiacetals and mentioning
confidence: 99%
“…Ramström’s research is centered on molecular recognition, in particular receptor–ligand interactions and complex chemical networks, and includes topics such as dynamic chemistry, synthesis and catalysis, nanomaterials, and sensors and interfaces. He has reported in Angewandte Chemie on the racemase‐type activity of B. cepacia lipase,7a and in Chemistry—A European Journal on lipase‐catalyzed γ‐lactonization 7b…”
Section: Awarded …︁mentioning
confidence: 99%
“…18,[21][22][23][24]27,28 It was shown that similar enantiomeric excesses (ees) could be obtained with both solvents; however, in toluene, higher conversions and reaction rates were observed. Among the enzymes tested, viz.…”
mentioning
confidence: 96%